A Trade War That is Unwarranted. Issue 5 (13th September 2018) - Yu, Yongding
Abstract: The Trump Administration has presented three major reasons to justify the initiation of a China–US trade war: China's large trade surplus against the US, China's failure to comply with World Trade Organization (WTO) commitments and China's unreasonable acquisition of US technology and theft of intellectual property rights. The fundamental cause of the US trade deficit is its persistent saving deficiency. China has complied with WTO commitments, although there remains significant room for improvement. The case against China for the so‐called unfair acquisition of foreign technologies and cyber‐enabled intellectual property rights theft is weak at best, although China needs to redouble its effort in protecting intellectual property rights. President Trump's trade war will not drive China to abandon its resolve to catch up to the advanced economies. China is ready to fight a war of attrition. Unfortunately, both sides – as well as the rest of the world – will incur heavy losses in the process.